2011
DOI: 10.1021/je101161d
|View full text |Cite
|
Sign up to set email alerts
|

Critical Assessment of CO2 Solubility in Volatile Solvents at 298.15 K

Abstract: Fifteen different low molar mass compounds are assessed as CO 2 solvents based on bubble-point loci on the solventrich end (0.6 to 1.0 solvent wt fraction) of the CO 2 -solvent pressure-composition diagram at 298.15 K. Four of the five best solvents (in descending order of solvent strength on a mass fraction CO 2 dissolved basis), acetone, methyl acetate, 1,4-dioxane, and 2-methoxyethyl acetate, are oxygen-rich, low molar mass species possessing one or more oxygen atoms in carbonyl, ether, and/or acetate group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 48 publications
4
32
0
Order By: Relevance
“…Interestingly, when using 1,4‐dioxane as the co‐solvent, the reaction resulted in the formation of CA‐1 and LA‐1 with an increased TON of 275 and 221 (entry 7). This improved reactivity of the catalytic system can be largely attributed to the higher CO 2 solvation capacity of 1,4‐dioxane and paves the way to a self‐breeding system with the application of the reaction product 1,3‐dioxane as solvent . Running the reaction for a longer time (40 h) resulted in an increased formation of CA‐1 (TON=239) and the minor production of LA‐1 (TON=100), hinting towards a subsequent intramolecular trans ‐etherification of LA‐1 to CA‐1 (entry 8).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, when using 1,4‐dioxane as the co‐solvent, the reaction resulted in the formation of CA‐1 and LA‐1 with an increased TON of 275 and 221 (entry 7). This improved reactivity of the catalytic system can be largely attributed to the higher CO 2 solvation capacity of 1,4‐dioxane and paves the way to a self‐breeding system with the application of the reaction product 1,3‐dioxane as solvent . Running the reaction for a longer time (40 h) resulted in an increased formation of CA‐1 (TON=239) and the minor production of LA‐1 (TON=100), hinting towards a subsequent intramolecular trans ‐etherification of LA‐1 to CA‐1 (entry 8).…”
Section: Methodsmentioning
confidence: 99%
“…This improved reactivity of the catalytic system can be largely attributed to the higher CO 2 solvation capacity of 1,4-dioxane and paves the way to as elf-breeding system with the application of the reaction product 1,3-dioxane as solvent. [11] Running the reaction for al ongert ime (40 h) resulted in an increased formation of CA-1 (TON = 239) and the minor production of LA-1 (TON = 100), hinting towards as ubsequent intramolecular trans-etherification of LA-1 to CA-1 (entry 8). More detailed information on the optimization of reaction conditions and parameters can be found in the Supporting Information).…”
mentioning
confidence: 99%
“…However, the solubility of CO 2 in water is quite low (i.e., 0.033 mol L −1 at 25°C under 1 atm) [67], which disfavors the adsorption of CO 2 to catalysts and largely suppresses the reduction process. It has been reported that CO 2 molecules are substantially more soluble in non-aqueous organic solvents [68]. For instance, the solubility of CO 2 in methanol is nearly 5 times higher than that in water under ambient conditions.…”
Section: Solventmentioning
confidence: 99%
“…Acetone contains two methyl groups (CH 3 ) located at each side. It was reported from the molecular orbital calculations based on the density functional theory that the carbonyl group of the acetone has specific interactions with CO 2 [25]. The local polarity of the quadrupole moment in the linear CO 2 structure enhances the solubility of slightly polar molecules in high pressure CO 2 .…”
Section: Mixture Design With Solvents To Reduce Mmpmentioning
confidence: 99%
“…Acetone provides the increased affinity of the solution towards oil phase. By dissolving acetone in CO 2 , the solubility parameter of CO 2 becomes closer to that of oil phase and the methyl groups of acetone (lipophilic moiety) increases the affinity towards oil phase [23][24][25]. On the other hand, methanol has the largest polarity among the additives so that its performance is poor, for they are non-symmetric protic solvents.…”
Section: Mixture Design With Solvents To Reduce Mmpmentioning
confidence: 99%